The Economic Crisis and Residential Electricity Consumption in Spanish Provinces: A Spatial Econometric Analysis - Leticia Blázquez; Fabian Heimsch; Massimo Filippini (ETH Zurich, CER-ETH - Center of Economic Research, 2013)
This paper presents an empirical analysis of residential electricity demand considering the existence of spatial effects. This analysis has been performed using aggregate panel data at the province level for 46 Spanish provinces for the period from 2001 to 2009. For this purpose, we estimated a log-log demand equation using a spatial autoregressive model with autoregressive disturbances (SARAR). The purpose of this empirical analysis is to determine the influence of price, income, and spatial spillovers on residential electricity demand in Spain. We are particularly interested in analyzing the impact of household disposable income variation across provinces observed during the economic crisis period from 2008-2009. The estimation results show relatively high income elasticity and relatively low price elasticity. Furthermore, the results show the presence of spatial effects in Spanish residential electricity consumption.
Keywords: D; D2; Q; Q4; R2; 330; residential electricity demand; aggregate panel data; spatial economic effects; economic crisis; spatial econometrics; Energiekonsum; Räumliche Verteilung; Wirtschaftskrise; Panel; Spanien